Prevalence and awareness of vaping among the students: A cross-sectional study from a university campus in the Perak state of Malaysia - Htwe, Than Than; Ismail, Sabaridah; Isqandar, Ahmad Johan A.; Wildan, Ahmad Yusuf R.; Zuhaily, Arief A.; Nurhaziqah, R.; Niqman, Nur A.; Danish, Wan Muhammad Aqlan (Journal of Biomedical Sciences, 2024)
Background: In recent years, there has been a remarkable increase in the vaping trend within the community, which has become a concerning issue in public health. This study aims to determine the prevalence and awareness of vaping among university students and its associated factors.Material and methods: A cross-sectional questionnaire-based study was conducted on vaping habits in Universiti Kuala Lumpur Royal College of Medicine Perak (UniKL RCMP). The questionnaire was distributed online, and 244 students from three levels of education (degree, diploma and foundation programmes) filled it out.Results:101 (41.4%) males and 143 (58.6%) females aged 18-30 participated. Most respondents were from urban areas 145 (59.4%). Most of the volume consumed through vaping was 10.1-15.0 ml, with a frequency of 17 (29.8%). Regarding how often they had vaped, were ‘never’: 164 (67.8%). Most responded as a “social trend’ 74 (30.3%) as a primary response for vaping.Conclusion: The prevalence and awareness of e-cigarettes present a severe problem among young adults. Implementing more holistic intervention measures is a necessity for prevention and awareness of the rising trend in e-cigarette smoking within the community.